PENGANGKATAN URANG BAINDUAK PADA MASYARAKAT MINANGKABAU DI NAGARI AMPANG KURANJI - JOHAN AGUSTIAN (PREMISE LAW JURNAL, 2014)
ABSTRACT Appointment urang bainduak the Minangkabau community in Nagari Ampang Kuranji, generally occurs in adults who come from outside Dharmasraya. This study is a descriptive analysis, the sociological juridical approach. Collection technique is done by means of library research and field research. The data used are primary data and secondary data. The data were analyzed qualitatively. The final conclusion is, that the legal basis for the appointment of urang bainduak is based on customary law which is derived from indigenous Minangkabau “adat nan taradat”. Legal consequences are urang bainduak as the biological child protection; urang bainduak not the heir of the adoptive parents will be but the beneficiary of his biological parents; urang bainduak do not break (nasab) with her ​​biological family; urang bainduak unmarried forbidden to marry the brother adopted. Keywords: Appointment, Urang Bainduak, Indigenous Minangkabau